The financial benefits of a firm's affiliation with the UN Global Compact. (19th December 2014) - Coulmont, Michel; Berthelot, Sylvie
<x xml:space="preserve">Abstract</x> Since it was first introduced 13 years ago in 2000, the UN Global Compact has become the world's largest voluntary corporate responsibility initiative. The benefits for companies that have voluntarily affiliated with the UN Global Compact have been little documented from an empirical perspective, especially regarding the integration of this information by capital markets. This study attempts to address this question, drawing on a sample of French companies listed on the SBF 250 index. Results suggest that, within the French context at least, investors significantly value a firm's affiliation with the UN Global Compact. In addition, the firms affiliated are those that appear to present the least risk.